Variation in the Use of Active Surveillance for Low-Risk Prostate Cancer Across US Census Regions - Al Hussein Al Awamlh, Bashir; Patel, Neal; Ma, Xiaoyue; Calaway, Adam; Ponsky, Lee; Hu, Jim C.; Shoag, Jonathan E. (Frontiers in Oncology, 2021)
Background Substantial geographic variation in healthcare practices exist. Active surveillance (AS) has emerged as a critical tool in the management of men with low-risk prostate cancer. Whether there have been regional differences in adoption is largely unknown. Methods The SEER “Prostate with Watchful Waiting Database” was used to identify patients diagnosed with localized low-risk prostate cancer and managed with AS across US census regions between 2010-2016. Multivariable logistic regression models were used to determine the impact of region on undergoing AS and factors associated with AS use within each US census region. Results Between 2010-16, the proportion of men managed with AS increased from 20.8% to 55.9% in the West, 11.5% to 50.0% in Northeast, 9.9% to 43.4% in the South and 15.1% to 56.2% in Midwest (p< 0.0001). On multivariable analysis, as compared to the West, men in all regions were less likely to undergo AS (p<0.001). Black men in the West (OR 1.36, 95%CI 1.25-1.49) and Midwest (OR 1.62, 95%CI 1.35-1.95) were more likely to undergo AS, but less likely in Northeast (OR 0.80, 95%CI 0.69-0.92). Men with higher socioeconomic status (SES) were more likely to undergo AS in the West (OR 1.47, 95%CI 1.39-1.55), Northeast (OR 1.57, 95%CI 1.36-1.81) and South (OR 1.24, 95%CI 1.13-1.37) but not in the Midwest (OR 0.85, 95%CI 0.73-0.98). Conclusions We found striking regional differences in the uptake of AS according to race and SES. Geography must be taken into consideration when assessing barriers to AS use.